การใช้เศษคอนกรีตและหินแกรนิตเพื่อกำจัดสารประกอบไนโตรเจนและฟอสฟอรัสในน้ำเสียชุมชนที่ผ่านการบำบัดขั้นที่สองแล้ว - พิศณุ ดวงกระโทก (จุฬาลงกรณ์มหาวิทยาลัย, 2001)
The efficiency of filtration using concrete rubbish and granite rock as filter medias for treatment of wastewater from secondary treatment process is studied under various circumstances. The filter media sizes under consideration are 1.0 and 3.0 mm. and the filtration rates are 1 and 3 m3/m2-hr. The water parameters measured are pH, turbidity, suspended solid, total phosphorus, TKN and COD. It is found that filtration using concrete rubbish as filter media provides high efficiency in removal of total phosphorus and suspended solid, but low efficiency in TKN and COD removal. Whereas filtration using granite rock as filter media provides high efficiency in suspended solid removal, but low efficiency in phosphorus, TKN and COD removal.